Tectonics and sedimentation in convergent margin basins: an example from the Tertiary Elazig basin, Eastern Turkey - Aksoy, E; Türkmen, I; Turan, I (Pergamon-Elsevier Science Ltd, 2005)
The Tertiary units of the Elazig basin consist of Lower Paleocene continental deposits, Upper Paleocene-Lower Miocene marine deposits and Pliocene-Quaternary continental deposits. In the Early Paleocene, alluvial fan deposits developed at the front of a thrust related to southward emplacement of Permo-Triassic metamorphic rocks onto Upper Cretaceous magmatic rocks. Marine conditions developed in the basin as a result of an extensional regime that started during the Late Paleocene and continued until Early Miocene time. In the Elazig basin, Late Paleocene-Early Eocene time is represented by shallow-marine limestones while the Middle-Late Eocene sequence includes clastic and calcareous rocks of shelf, slope, slope apron and basin plain environments. The Tethys sea became shallower and retreated to the north during the Oligocene. Shallow-marine carbonate and clastics were deposited in the basin from Oligocene to Early Miocene time. Fluvial and lacustrine deposits accompanied by Early Pliocene volcanism filled E-W trending intermontane basins related to N-S tension beginning in the Early Pliocene. Alluvial fan and fluvial deposits accumulated during the Plio-Quaternary and were related to ENE-WSW aligned folds and thrusts. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Pliocene; Eocene; Miocene